2011
DOI: 10.1007/s00425-011-1506-9
|View full text |Cite
|
Sign up to set email alerts
|

The PAL2 promoter activities in relation to structural development and adaptation in Arabidopsis thaliana

Abstract: Phenylalanine ammonia lyase (PAL) plays a major role in plant growth, development and adaptation. In Arabidopsis thaliana, the enzyme is encoded by four genes, namely PAL1, PAL2, PAL3, and PAL4 with PAL1 and PAL2 being closely related phylogenetically and functionally. PAL1 promoter activities are associated with plant development and are inducible by various stress agents. However, PAL2 promoter activities have not been functionally analysed. Here, we show that the PAL2 promoter activities are associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…These two Arabidopsis genes are involved in lignifications of the vascular system and in phenylpropanoids synthesis in response to stress and pathogens [4648]. A blastn analyses of the four hemp PAL ESTs isolated by van den Broeck et al [40] vs. nt database indicated that they correspond with at least two different genes.…”
Section: Resultsmentioning
confidence: 99%
“…These two Arabidopsis genes are involved in lignifications of the vascular system and in phenylpropanoids synthesis in response to stress and pathogens [4648]. A blastn analyses of the four hemp PAL ESTs isolated by van den Broeck et al [40] vs. nt database indicated that they correspond with at least two different genes.…”
Section: Resultsmentioning
confidence: 99%
“…miR319a was more abundant in low-TPC samples than in high-TPC samples at the bolting with tiny flower bud stage, while the expression of its predicted target genes PHYA and BZIP25 was down-regulated in low- as compared to high-TPC samples from both sites; both genes play an important role in influencing photomorphogenesis, efficiency of phosphorus utilization, and seed development [79,80,81,82]. We also found that numerous other genes predicted to be related to nitrogen and carbon pathways, such as PAL2 [83], KIN10 [84], and CAS1 [85], were differentially expressed between the two groups based on the differential expression of miR319a. Members of the miR827 family were up-regulated in flower buds of high-TPC as compared to low-TPC plants, while their target genes AMK2 , XPO1A , PATL1 , and KNAT5 were down-regulated.…”
Section: Discussionmentioning
confidence: 96%
“…This suggests that compounds that use L-phenylalanine as a biosynthetic intermediate can be better induced under moderate stress conditions. The unigenes UN059693, UN073057, UN061336 and UN064046, homologues of the enzyme phenylalanine ammonia lyase (PAL), are part of a multigenic family involved in an interesting defense network in plants, which is induced in response to various environmental stresses, such as nutrient deficiency [ 34 , 35 , 36 ]. The expression of some members of this family is correlated with the induction of genes involved in the defense response of plants and in the response to oxidative stress [ 35 , 37 ].…”
Section: Resultsmentioning
confidence: 99%